Belajar Menyenangkan Dengan Serius Tapi Santai di Panti Asuhan Rapha-El - Lestina Sitanggang; Malida Putri (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Field Work Practice is one of the concrete evidences in the embodiment of the tri dharma of higher education, namely the expected service through street vendors is able to have a positive impact on the surrounding community. Apart from the objectives of street vendors, which are expected to be able to have a positive impact, they are also able to make students become independent. Through this street vendors too, it is hoped that the practitioner will be able to awaken the importance of education. Therefore, education is able to bring us to achieve the goals we dream of. Practitioners undergo street vendors using general / general stages through the mini project that is carried out. The stages are the assessment stage, the program planning stage, the intervention stage, the program evaluation stage and the termination stage.